Analisis Normatif Terhadap Implementasi Peraturan Presiden Republik Indonesia Nomor 72 Tahun 2021 Tentang Percepatan Penurunan Stunting - Sitohang, Dahlan; Lestari, Mastuti Widi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Stunting is a significant issue in Indonesia, greatly affecting children's health and development. To address this, collaboration between ministries and institutions, as well as a focused effort on the first 1,000 days of a child's life, is essential for successfully reducing stunting. Therefore, analyzing the implementation of relevant policies is crucial to improving their effectiveness. This study aims to examine the implementation of Presidential Regulation of the Republic of Indonesia Number 72 of 2021, which focuses on the acceleration and reduction of stunting. The research uses a descriptive method with a qualitative approach to comprehensively analyze the data, aiming to understand the context and identify challenges and successes in the regulation's implementation. The study finds that the Indonesian government, with strong commitment from the President and Vice President, is making efforts to reduce stunting rates through prevention and treatment programs targeting toddlers, pregnant women, and breastfeeding mothers, particularly during the critical First 1,000 Days of Life. Presidential Regulation Number 72 of 2021 provides the framework for accelerating stunting reduction, including a nutrition intervention program, supplementary food provision, and improved access to sanitation. The national strategy consists of five main pillars and involves various sectors working together to achieve the goal of reducing stunting by 14% by 2024.